Peran Sistem Pengendalian Internal dalam Meminimalkan Risiko pada Siklus Pembelian: Studi Kasus The Wing Es-Hotel - Annisa Sagala; Rayyan Firdaus (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Internal control systems have a crucial role in minimizing risks that can occur in the purchasing cycle in organizations, including in the hotel industry. This research aims to analyze the role of the internal control system in mitigating risks in the purchasing cycle at The Wing Es-Hotel. This research uses a case study approach with data collected through interviews, observation and documentation. The research results show that implementing an effective internal control system can identify potential risks such as errors in supplier selection, non-conformity of goods received, and uncontrolled expenditure. By having control elements such as proper authorization, authority and internal audit, these risks can be minimized. This study provides recommendations for The Wing Es-Hotel to improve sustainability monitoring and evaluation of the internal control system to support operational efficiency financial losses